Efficiency of Airborne Sample Analysis Platform (ASAP) bioaerosol sampler for pathogen detection - Sharma, Anurag; Clark, Elizabeth; McGlothlin, James D.; Mittal, Suresh K. (Frontiers in Microbiology, 2015)
The threat of bioterrorism and pandemics has highlighted the urgency for rapid and reliable bioaerosol detection in different environments. Safeguarding against such threats requires continuous sampling of the ambient air for pathogen detection. In this study we investigated the efficacy of the Airborne Sample Analysis Platform (ASAP) 2800 bioaerosol sampler to collect representative samples of air and identify specific viruses suspended as bioaerosols. To test this concept, we aerosolized an innocuous replication-defective bovine adenovirus serotype 3 (BAdV3) in a controlled laboratory environment. The ASAP efficiently trapped the surrogate virus at 5 × 103 plaque-forming units (p.f.u.) [2 × 105 genome copy equivalent] concentrations or more resulting in the successful detection of the virus using quantitative PCR. These results support the further development of ASAP for bioaerosol pathogen detection.